CHARACTER EDUCATION IN FORMING STUDENT BEHAVIOR: A Viewpoint of Christian Religious Education Learning - Ester A. Tandana; Esti Koku Yowa; Novida Dwici Yuanri Manik (Didache: Jurnal Teologi dan Pendidikan Kristen, 2022)
Educational institutions become a central place to shape the character of children who are better than before through character education. Character education is a process of forming students into human beings with good character intact in the dimensions of reason, thinking, healthy, physically, spirituality, and a human heart. Character education carves the morals of students through the process of knowing goodness, loving-kindness, and practicing goodness. The process involves cognitive, emotional, and physical aspects so that noble character can be realized and carved into habits of the mint, heart, and hands. People who have a knowledge and knowledge orientation based on faith in Jesus Christ. A teacher carries out character education learning in the teaching and learning process by making students formulate questions actively, find learning resources, collect information, reconstruct facts, and present the results of reconstruction or improvement. Learning character education must be carried out by teachers by planning, implementing, and evaluating Christian religious education teachers not only provide information or knowledge to their students but Christian religious education teachers are expected to be able to guide and set good examples for students so that they can imitate and indirectly shape the character of children. In this paper, the author uses the literature study method to solve the problems in this research. This aims to find out how character education in shaping the behavior of students through learning Christian religious education. The results of the research are in building character, Christian Religious Education content must place Jesus Christ as the center of life and become the perfect role model for the character in their lives.   Lembaga pendidikan menjadi tempat sentral untuk membentuk karakter anak yang lebih baik dari sebelumnya melalui pendidikan karakter. Pendidikan karakter merupakan proses membentuk peserta didik menjadi manusia yang berkarakter baik utuh dalam dimensi akal, budi pekerti berpikir, sehat jasmani, rohani, dan berhati manusia. Pendidikan karakter mengukir akhlak peserta didik melalui proses mengetahui kebaikan, mencintai kebaikan, dan mengamalkan kebaikan. Proses tersebut melibatkan aspek kognitif, emosional dan fisik, sehingga akhlak mulia dapat terwujud mengukir menjadi kebiasaan pikiran, hati, dan tangan. Orang yang memiliki orientasi ilmu dan pengetahuan yang dilandasi dengan iman kepada Yesus Kristus. Seorang guru melaksanakan pembelajaran pendidikan karakter dalam proses belajar mengajar dengan cara: membuat peserta didik merumuskan pertanyaan secara aktif, menemukan sumber belajar, mengumpulkan informasi, merekonstruksi fakta, dan menyajikan hasil rekonstruksi atau perbaikan. Pembelajaran pendidikan karakter harus dilakukan oleh guru dari perencanaan, pelaksanaan, dan evaluasi. Guru pendidikan agama Kristen tidak hanya memberikan informasi atau pengetahuan saja kepada anak didiknya akan tetapi guru pendidikan agama Kristen diharapkan mampu untuk membimbing dan memberikan contoh yang baik kepada anak didik sehingga mereka dapat meneladani dan secara tidak langsung membentuk karakter anak. Dalam tulisan ini penulis menggunakan metode studi pustaka untuk memecahkan permasalahan dalam penelitian ini. Hal ini bertujuan untuk mengetahui bagaimana pendidikan karakter membentuk perilaku peserta didik melalui pembelajaran pendidikan agama Kristen. Hasil penelitian adalah dalam membangun karakter, konten Pendidikan Agama Kristen harus menempatkan Yesus Kristus sebagai pusat kehidupan dan menjadi panutan yang sempurna bagi karakter dalam kehidupan mereka.